Heterochromatin as an Important Driver of Genome Organization - Penagos-Puig, Andrés; Furlan-Magaril, Mayra (Frontiers in Cell and Developmental Biology, 2020)
Heterochromatin is a constituent of eukaryotic genomes with functions spanning from gene expression silencing to constraining DNA replication and repair. Inside the nucleus, heterochromatin segregates spatially from euchromatin and is localized preferentially towards the nuclear periphery and surrounding the nucleolus. Despite being an abundant nuclear compartment, little is known about how heterochromatin regulates and participates in the mechanisms driving genome organization. Here, we review pioneer and recent evidence that explores the functional role of heterochromatin in the formation of distinct chromatin domains and how failure in the molecular mechanisms forming heterochromatin leads to disarray of genome conformation and disease.